2023
DOI: 10.1128/msphere.00061-23
|View full text |Cite
|
Sign up to set email alerts
|

Virulent Brucella nosferati infecting Desmodus rotundus has emerging potential due to the broad foraging range of its bat host for humans and wild and domestic animals

Gabriela Hernández-Mora,
Carlos Chacón-Díaz,
Andres Moreira-Soto
et al.

Abstract: Desmodus rotundus, vampire bats, transmit dangerous infections, and brucellosis is a hazardous zoonotic disease, two adversities that coexist in the subtropical and tropical areas of the American continent. Here, we report a 47.89% Brucella infection prevalence in a colony of vampire bats inhabiting the tropical rainforest of Costa Rica. The bacterium induced placentitis and fetal death in bats. Wide-range phenotypic and genotypic characterization placed the Bruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…infection in various species of bats from different parts of the world, a pioneering study has demonstrated serologic evidence of Brucella infection in vampire bats ( Desmodus rotundus ) in Brazil ( 17 ). Importantly, during the course of this study, infection of Desmodus rotundus vampire bats with a novel Brucella species was described, and the newly identified species was named Brucella nosferati ( 18 ). Unfortunately, only formalin-fixed samples were available in this study, which prevented us from attempting isolation and characterization of the Brucella sp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…infection in various species of bats from different parts of the world, a pioneering study has demonstrated serologic evidence of Brucella infection in vampire bats ( Desmodus rotundus ) in Brazil ( 17 ). Importantly, during the course of this study, infection of Desmodus rotundus vampire bats with a novel Brucella species was described, and the newly identified species was named Brucella nosferati ( 18 ). Unfortunately, only formalin-fixed samples were available in this study, which prevented us from attempting isolation and characterization of the Brucella sp.…”
Section: Discussionmentioning
confidence: 99%
“…( 13 16 ). Importantly, anti- Brucella antibodies have been detected in vampire bats ( Desmodus rotundus ) in Brazil ( 17 ), and recently, a novel Brucella species has been identified infecting vampire bats in Costa Rica ( 18 ). Thus, the finding of genital lesions, which are known to be associated with Brucella infection in many animal species ( 10 12 ), in free-ranging bats prompted us to investigate the possibility of Brucella infection.…”
Section: Introductionmentioning
confidence: 99%